The correlation between whole body reaction time and the onset timing of lower extremity muscles during landing. Issue 4 (27th March 2011) - Sasaki, R; Urabe, Y; Yamanaka, Y; Fujii, E; Matsubayashi, Y
Abstract : Background: Quickness can be shown as whole body reaction time (WBRT) by measuring how quickly they can react for a stimulus. In addition, it is said that the onset timing of muscles contribute to stabilise joints and to prevent injury during the movement. Objective: The purpose of this study is to clarify the correlation between WBRT and the onset timing of muscles during landing. Design: Randomisation study. Setting: Youth sports. Participants: 15 healthy female college students volunteered in this study. Intervention: WBRT was defined as the duration from light stimulus to the both feet apart from the floor. The onset timing of muscles were measured by bilateral landing from the 40 cm height box with the electromyography (EMG). EMG data were collected from vastus medialis (VM), vastus lateralis (VL), semimembranosus (SM) and biceps femoris (BF). The onset timing of the muscle was visually identified as the first point, which was the EMG amplitude of 100 ms after the start of landing movement that exceeded the mean baseline activity by three SD. The definition of the baseline was set as the EMG amplitude of the 100 ms after the toe-off from the box. Main outcome measurements: The hypothesis was that there were the correlation between WBRT and the onset timing of muscles. Results: The mean±SD of WBRT was 331.8±45.6 ms. VM onset timing during landing was 243.7±78.3 ms, VL was 259.6±75.5 ms, SM was 191.7±86.2 ms, BF was 237.5±73.8 ms. There were correlations between WBRT and SM and BF onset timings (p<0.05). Conclusion: This study identified the correlation between WBRT and SM and BF onset timing. It might be possible to make SM and BF onset timing occur faster by reacting to certain stimulus faster.